Designations of the lectotypes for the oriental species of the genus Carpelimus Leach, 1819 (Coleoptera: Staphylinidae) - Gildenkov, Mikhail Yu. (Zootaxa, 2013)
The type material of the Oriental Carpelimus species from five museums have been investigated. Thirty four lectotypes are designated for the following species: Trogophloeus bengalensis Cameron, 1930; T. bicolor Cameron, 1940; T. calcuttanus Bernhauer, 1911; T. chatterjeei Cameron, 1930; T. congruus Cameron, 1930; T. coriaceus Cameron, 1930; T. flavipennis Cameron, 1930; T. formosae Cameron, 1940; T. formosanus Cameron, 1940; T. foveicollis Kraatz, 1859; T. gratus Cameron, 1930; T. halophiloides Cameron, 1918; T. javanicus Cameron, 1936; T. laticeps Cameron, 1930; T. lepidicornis Fauvel, 1904; T. littoralis Cameron, 1918; T. louwerensi Cameron, 1938; T. lucens Cameron, 1918; T. nitidipennis Cameron, 1919; T. palitans Cameron, 1930; T. pallidicornis Cameron, 1945; T. papuensis Fauvel, 1879; T. piceicollis Cameron, 1930; T. planicollis Bernhauer, 1902; T. praelongus Bernhauer, 1938; T. pusae Cameron, 1930; T. ruficornis Cameron, 1930; T. rufoniger Cameron, 1945; T. sadiyanus Cameron, 1945; T. saigonensis Cameron, 1940; T. scabrosus Kraatz, 1859; T. simplex Motschulsky, 1857; T. taprobanae Walker, 1859; T. trivialis Cameron, 1930. The genital figures for all species (except T. flavipennis) are presented.